Congenital Fibrinogen Disorders: An Update - de Moerloose, Philippe; Casini, Alessandro; Neerman-Arbez, Marguerite (Seminars in Thrombosis and Hemostasis, 2013)
Hereditary fibrinogen abnormalities comprise two classes of plasma fibrinogen defects: Type I, afibrinogenemia or hypofibrinogenemia, which has absent or low plasma fibrinogen antigen levels (quantitative fibrinogen deficiencies), and Type II, dysfibrinogenemia or hypodysfibrinogenemia, which shows normal or reduced antigen levels associated with disproportionately low functional activity (qualitative fibrinogen deficiencies). In afibrinogenemia and hypofibrinogenemia, most mutations of the FGA, FGB, or FGG fibrinogen encoding genes are null mutations. In some cases, missense or late truncating nonsense mutations allow synthesis of the corresponding fibrinogen chain but intracellular fibrinogen assembly and/or secretion are impaired. Afibrinogenemia is associated with mild-to-severe bleeding, whereas hypofibrinogenemia is most often asymptomatic. Thromboembolism may occur either spontaneously or in association with fibrinogen substitution therapy. Women with afibrinogenemia suffer from recurrent pregnancy loss but this can also occur in women with hypofibrinogenemia. Dysfibrinogenemia, caused mainly by missense mutations, is commonly associated with bleeding, thrombophilia, or both; however, most individuals are asymptomatic. Hypodysfibrinogenemia is a subcategory of this disorder. Even in specialized laboratories, the precise diagnosis of some fibrinogen disorders may be difficult. Determination of the molecular defects is important because it gives the possibility to confirm the diagnosis, to elaborate a diagnostic strategy, to distinguish in some cases that the patient is at risk of thrombosis rather than bleeding, and to enable prenatal diagnosis. However, genotype–phenotype correlations are not easy to establish. Replacement therapy is effective in treating bleeding episodes, but because the pharmacokinetics of fibrinogen after replacement therapy is highly variable among patients, it is important to adjust the treatment individually.
Keywords: bleeding disorder; fibrinogen; afibrinogenemia; dysfibrinogenemia; hypofibrinogenemia; thrombosis